Impact of postoperative femorotibial axis on functional outcomes in unicompartmental knee arthroplasty - Kokturk, Anil; Tokgoz, Mehmet Ali; Cigercioglu, Nazli Busra; Baltaci, Gul; Ozer, Hamza (Turkish Joint Diseases Foundation, 2024)
Objectives: This study aimed to compare the functional outcomes of patients undergoing fixed -bearing medial unicompartmental knee arthroplasty (UKA) classified as either varus or neutral based on their postoperative femorotibial angle (FTA), with the goal of evaluating the impact of FTA on functional results. Patients and methods: A total of 38 knees of 35 patients (27 females, 8 males; mean age: 63.6 +/- 7.1 years; range, 52 to 75 years) were included in this retrospective study. The data was collected between December 15, 2020, and January 15, 2021. Patients were categorized into two groups based on their postoperative FTA. The neutral group consisted of patients with an FTA range of 5.1 degrees to 7.4 degrees, while the varus group included patients with an FTA range of 0.1 degrees to 4.8 degrees. Knee Outcome Osteoarthritis Score (KOOS), Visual Analog Scale (VAS) scores, sit to stand test results, and six minute walk test data were analyzed. Results: The mean follow-up was 42.0 +/- 19.3 months. The postoperative VAS score for the varus group was 0.95 +/- 0.99, whereas the neutral group had a VAS score of 2.19 +/- 1.83 (p=0.021). The mean KOOS for the varus group was 88.01 +/- 7.88, whereas the neutral group had a mean KOOS score of 78.46 +/- 13.69 (p=0.006). Conclusion: In patients undergoing UKA, mild varus alignment could yield superior early and midterm functional outcomes compared to a neutral femorotibial angle.
Keywords: Functional outcomes; medial compartment gonarthrosis; osteoarthritis; unicompartmental knee arthroplasty